Answer:
710
Step-by-step explanation:
Answer:
The radical notation is ![3x\sqrt[3]{y^2z}](https://tex.z-dn.net/?f=3x%5Csqrt%5B3%5D%7By%5E2z%7D)
Step-by-step explanation:
Given
![\sqrt[3]{27 x^{3} y^{2} z}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B27%20x%5E%7B3%7D%20y%5E%7B2%7D%20z%7D)
Step 1 of 1
Write the expression using rational exponents.
![\sqrt[n]{a^{m}}=\left(a^{m}\right)^{\frac{1}{n}}](https://tex.z-dn.net/?f=%5Csqrt%5Bn%5D%7Ba%5E%7Bm%7D%7D%3D%5Cleft%28a%5E%7Bm%7D%5Cright%29%5E%7B%5Cfrac%7B1%7D%7Bn%7D%7D)
![=a^{\frac{m}{n}}:\left({27 x^{3} y^{2} z})^{\frac{1}{3}}](https://tex.z-dn.net/?f=%3Da%5E%7B%5Cfrac%7Bm%7D%7Bn%7D%7D%3A%5Cleft%28%7B27%20x%5E%7B3%7D%20y%5E%7B2%7D%20z%7D%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D)
![$(a \cdot b)^{r}=a^{r} \cdot b^{r}:(27)^{\frac{1}{3}}\left(x^{3}\right)^{\frac{1}{3}} \cdot\left(y^{2}\right)^{\frac{1}{3}} \cdot(z)^{\frac{1}{3}}$](https://tex.z-dn.net/?f=%24%28a%20%5Ccdot%20b%29%5E%7Br%7D%3Da%5E%7Br%7D%20%5Ccdot%20b%5E%7Br%7D%3A%2827%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%5Cleft%28x%5E%7B3%7D%5Cright%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%20%5Ccdot%5Cleft%28y%5E%7B2%7D%5Cright%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%20%5Ccdot%28z%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%24)
![=$(3^3)^{\frac{1}{3}}\left(x^{3}\right)^{\frac{1}{3}} \cdot\left(y^{2}\right)^{\frac{1}{3}} \cdot(z)^{\frac{1}{3}}$](https://tex.z-dn.net/?f=%3D%24%283%5E3%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%5Cleft%28x%5E%7B3%7D%5Cright%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%20%5Ccdot%5Cleft%28y%5E%7B2%7D%5Cright%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%20%5Ccdot%28z%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%24)
![$=\left(3\right)\left(x}\right)} \cdot\left(y}\right)^{\frac{2}{3}} \cdot(z)^{\frac{1}{3}}$](https://tex.z-dn.net/?f=%24%3D%5Cleft%283%5Cright%29%5Cleft%28x%7D%5Cright%29%7D%20%5Ccdot%5Cleft%28y%7D%5Cright%29%5E%7B%5Cfrac%7B2%7D%7B3%7D%7D%20%5Ccdot%28z%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%24)
![$=3x \cdot(y)^{\frac{2}{3}} \cdot(z)^{\frac{1}{3}}$](https://tex.z-dn.net/?f=%24%3D3x%20%5Ccdot%28y%29%5E%7B%5Cfrac%7B2%7D%7B3%7D%7D%20%5Ccdot%28z%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%24)
Simplify ![$3 x \cdot(y)^{\frac{2}{3}} \cdot(z)^{\frac{1}{3}}$](https://tex.z-dn.net/?f=%243%20x%20%5Ccdot%28y%29%5E%7B%5Cfrac%7B2%7D%7B3%7D%7D%20%5Ccdot%28z%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%24)
![$=3 x \sqrt[3]{y^{2} z}$](https://tex.z-dn.net/?f=%24%3D3%20x%20%5Csqrt%5B3%5D%7By%5E%7B2%7D%20z%7D%24)
Learn more about radical notation, refer :
brainly.com/question/15678734
Answer:
lol fr
Step-by-step explanation:
Set it up as an equation: 12 + 6x = 47
(x is the reduced fee)
12 + 6x = 47
12 - 12 + 6x = 47 - 12
6x = 35
x = 35/6
x = 5.83 repeating (only the 3 is repeating)
Answer: 8 inches
Step-by-step explanation: So you know that to get the circumference of a circle is 2πr, right? So you divide 16 by 2 to get your radius. So that's how you 8 inches.